Bosnia and Herzegovina : Technical Assistance Report-Government Finance Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission about improving government finance statistics (GFS) for decision making in the Republic of Srpska, Bosnia and Herzegovina. It was found that a number of weaknesses of institutional arrangements needed to compile GFS in Bosnia and Herzegovina have yet to be resolved. Although collaboration between units involved in the compilation of GFS is well established in the Republic of Srpska, collaboration between the Bosnian institutions at the entity level and the state institutions lack fully the (in)formal prerequisites to support comprehensive and adequate fiscal data reporting. Particularly the sharing between institutions of data, metadata, and supporting information required for the accurate, timely, efficient, and auditable compilation of GFS needs strengthening.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CR; Government Finance Statistic; Government; ISCR; RS GFS Compilation; Bosnia and Herzegovina